Generalidades sobre la paloma común: historia, biología y salud (2023)
Indeed, in many countries, including Colombia, there has been controversy between those who sympathize with pigeons and those who consider them to be a plague that spreads diseases, invades, deteriorates, and affects the architecture of squares, cathedrals, parks, and buildings. Cultural roots cause people to have different perceptions about pigeons. However, from the perspective of animal welfare, the concept of animals requiring comprehensive care is defended, which involves: health status, population control, nutritional management, environmental impact, and even the epidemiological risk it represents for the community. In this sense, the Antonio Nariño University (UAN) has undertaken the challenge of generating and compiling relevant information regarding the species of pigeons (C. livia) and their role in the anthropic or urban environment.